Schizophrenia a very short introduction - Frith, Christopher D.; Johnstone, Eve C. (Oxford : Oxford University Press, 2003)
This book describes what schizophrenia is really like, how the illness progresses, and the treatments that have been applied. It also summarises the most up-to-date knowledge about the biological bases of this disorder.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Schizophrenia -- Popular works; Schizophrenia -- Case studies